2000
DOI: 10.3354/dao041135
|View full text |Cite
|
Sign up to set email alerts
|

Associations between epidermal thionin-positive cells and skin parasitic infections in brown trout Salmo trutta

Abstract: The dynamics of the densities of epidermal thionin-positive cells (putative mast cells) in the skin of brown trout fry were investigated during experimental infections with the skin parasites Ichthyophthirius multifilus (Ciliophora) and Gyrodactylus derjavini (Monogenea). It was shown that the metachromatic thionin-stained cells were extremely sensitive to parasite exposure, as the density of cells in the skin of trout decreased markedly after exposure to the pathogens. As early as 7 d post infection the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It has been speculated that eosinophilic granular cells and thionin-positive cells are identical cells with different staining characteristics following different fixations, and that these cells are fish mast cell homologues [24]. Brown trout thionin-positive putative mast cells were shown to degranulate after 7 days of infection with I. multifiliis [25]. In the infections of carp with I. multifiliis, infiltration of neutrophils and later eosinophilic granular cells was seen in the inflamed skin [9,10].…”
Section: Discussionmentioning
confidence: 97%
“…It has been speculated that eosinophilic granular cells and thionin-positive cells are identical cells with different staining characteristics following different fixations, and that these cells are fish mast cell homologues [24]. Brown trout thionin-positive putative mast cells were shown to degranulate after 7 days of infection with I. multifiliis [25]. In the infections of carp with I. multifiliis, infiltration of neutrophils and later eosinophilic granular cells was seen in the inflamed skin [9,10].…”
Section: Discussionmentioning
confidence: 97%
“…Because of the low mucous cell density the cornea was associated with parasite colonization during a host response. Further, it has been shown that the epidermis of the brown trout cornea also lacks the putative immunologically relevant mast cells (Sigh & Buchmann 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This may well be so (Buchmann 1999; Buchmann & Lindenstrøm 2002) and the predilection of G. derjavini for the corneal surface in unsuitable hosts also points to this. The cornea was suggested by Buchmann & Bresciani (1998) and Sigh & Buchmann (2000) to represent an immuno‐privileged site for gyrodactylids parasitizing responding or unsuitable hosts. The cohabitation system using exposure to a high number of gyrodactylids was suitable, in contrast to the isolated infections with only a few parasites, for analysis of this hypothesis.…”
Section: Isolated Single Parasite Infections Populations Of Gyrodactmentioning
confidence: 99%